Hydrogen/Deuterium Exchange Mass Spectrometry of Heme-Based Oxygen Sensor Proteins - Vávra, Jakub; Sergunin, Artur; Stráňava, Martin; Kádek, Alan; Shimizu, Toru; Man, Petr; Martínková, Markéta (Methods in molecular biology (Clifton, N.J.), 2023)
Hydrogen/deuterium exchange (HDX) is a well-established analytical technique that enables monitoring of protein dynamics and interactions by probing the isotope exchange of backbone amides. It has virtually no limitations in terms of protein size, flexibility, or reaction conditions and can thus be performed in solution at different pH values and temperatures under controlled redox conditions. Thanks to its coupling with mass spectrometry (MS), it is also straightforward to perform and has relatively high throughput, making it an excellent complement to the high-resolution methods of structural biology. Given the recent expansion of artificial intelligence-aided protein structure modeling, there is considerable demand for techniques allowing fast and unambiguous validation of in silico predictions; HDX-MS is well-placed to meet this demand. Here we present a protocol for HDX-MS and illustrate its use in characterizing the dynamics and structural changes of a dimeric heme-containing oxygen sensor protein as it responds to changes in its coordination and redox state. This allowed us to propose a mechanism by which the signal (oxygen binding to the heme iron in the sensing domain) is transduced to the protein's functional domain.
Keywords: Ligand binding; Hydrogen/deuterium exchange; Deuterium Exchange Measurement; hem; Oxygen; vodík; Hydrogen; Signal transduction; Heme-containing oxygen sensors; Mass Spectrometry; vodík-deuteriová výměna; hemoproteiny; Deuterium; Artificial Intelligence; kyslík; Hemeproteins; Globin-coupled histidine kinase; Mass spectrometry; umělá inteligence; Protein conformational dynamics; hmotnostní spektrometrie; Heme; deuterium